Exploring the Entrepreneurial Intention of Female University Students - Jamleea, Norzalina; Ridzuan, Mohd Rozaimy (International Business Education Journal, 2021)
One of today’s most hotly debated issues is whether female college students can become successful entrepreneurs in today’s global economy. Fierce competition between job applicants in today’s developing economy challenged many female graduates despite their aim to secure jobs, leading to entrepreneurship as an immediate solution. Entrepreneurship intentions of students have been linked to future entrepreneurial behavior, according to some research. Therefore, this article investigates the factors that contribute to the entrepreneurial intentions of female students at UiTM Dungun. The study utilizes the Theory of Planned Behavior (TPB). A total of 127 female university students were surveyed in this study. The students were given a set of surveys to rate their perceptions of entrepreneurial intentions. Their ratings were gathered and analyzed using SPSS Software. Pearson Correlation analysis was employed in this study to mesure the relationship between TPB factors and the dependent variable. The findings reveal that the entrepreneurial intention of female university students at UiTM Dungun is linked to all three factors of TPB (attitude, subjective norms, and perceived behavioral control). Researchers anticipate these findings will shed light on the phenomena of female university students expressing entrepreneurial aspirations.